PENERAPAN KNOWLEDGE MANAGEMENT SYSTEM DENGAN METODE MOST ADMIRED KNOWLEDGE ENTERPRISE (MAKE) PADA WEB TIM TUGAS AKHIR BAAK BSI - Muhammad Fahmi (Jurnal Teknik Informatika, 2015)
Abstract— Knowledge Management is a process that coordinates The use of The information, Knowledge and experience. Given in Tim Tugas Akhir BAAK BSI especially The lack of data Management and information that is easy to work, which leads to The same problem keeps recurring, Then made Knowledge sharing to manage data and information work. Effectiveness is needed in sharing The information. Hence, The authors sought to analyze site usage Knowledge Management that have been used from 2011 until now in Tim Tugas Akhir BAAK, How a Web application as a Knowledge Management System. The author uses descriptive research methods were conducted in Team Final BAAK BSI and supported by The method of The Most Admired Knowledge Enterprise (MAKE). Increasing The effectiveness of The final team members after using The Web "Tim TA" also has an effect on The improvement of The effectiveness of teamwork and team success in implementing Knowledge Management System (KMS). It concluded that Tim Tugas Akhir BAAK BSI has become a team that successfully implemented a Knowledge Management System (KMS).